PENDIDIKAN KARAKTER: AKTIVITAS KETERLIBATAN SUKARELAWAN MUDA ERA MODERN BEKERJA SECARA DARING DAN LURING - Muhammad Mona Adha; Eska Prawisudawati Ulpa (Universitas Sriwijaya, 2020)
Abstract: Young people participation would be runs to the maximum by being given the opportunity and place to be creative carried out as volunteers. The experience and learning process of working both online and offline voluntarily can increase the knowledge, practical skills, and experience of every volunteer. Qualitative research with an ethnographic approach is implemented to find the context and social interactions that occur between volunteers and the environment in which they are active. Opportunities for self-development through acts of sincere and noble service become significant to continue to be developed in the midst of society and become a habituation as a form of strengthening character and character so that character education can continue to be turned on and become a servant for themselves and for people around them.